Pengaruh Delegasi Wewenang, Penempatan dan Lingkungan Kerja terhadap Kinerja Pegawai - Alfian Anjasmara; Pompong B. Setiadi; Sri Rahayu (Al-Buhuts, 2022)
This study analyzes the effect of authority, placement, and work environment on employee performance. The research was aimed at employees of the logistics bureau of the East Java regional police. The research respondents totaled 55 people with the type of research sample selection, namely purposive sampling or determining the sample based on the research objectives. The research method applied is a survey using a questionnaire with reference to the Likert scale and the type of research is explanatory research. The data analysis method applies multiple linear regression, hypothesis testing, and the coefficient of determination. The data processing stage used the IBM Version 25 Statistical Product and Service Solutions (SPSS) application. The results showed that the placement and work environment variables had a partial effect, while the authority variable had no partial effect on employee performance.